NF-κB inhibitors impair platelet activation responses - Malaver Marín, Elisa (2009)
Background: Although platelets are anucleated cells, they express several transcription factors that exert non-genomic functions, including the positive and negative regulation of platelet activation. NF-κB is a major transcriptional regulator of genes involved in survival, proliferation and inflammation. Objective: Because platelets play a critical role not only in hemostasis, but also in inflammation and tumor progression, we evaluated the role of NF-κB in platelet physiology. Results: Immunofluorescence, Western blotting and ELISA studies revealed that platelets express IκBα and NF-κB, and that stimulation with thrombin triggers IκBα phosphorylation and degradation and the binding of platelet NF-κB p65 subunit to synthetic olignoucleotides containing the consensus sequence for NF-κB. Two specific unrelated inhibitors of NF-κB activation, BAY 11-7082 and Ro 106-9920, reduced PAC-1 and fibrinogen binding to integrin αIIbβ3 and restricted platelet spreading on immobilized fibrinogen. Both inhibitors impaired aggregation mediated by ADP, epinephrine, collagen or thrombin, but not arachidonic acid. ATP release, TXB2 formation, P-selectin expression, ERK phosphorylation and cPLA2 activity stimulated by thrombin were reduced in BAY 11-7082- or Ro 106-9920-treated platelets. Although bleeding time was not affected, ADP-induced platelet aggregation was impaired in mice treated with BAY 11-7082. Conclusions: Our results suggest that NF-κB may be a novel mediator of platelet responses. The blockade of platelet function by NF-κB inhibitors might be relevant in those clinical situations where these drugs are being considered for anti-tumor and/or anti-inflammatory therapy. © 2009 International Society on Thrombosis and Haemostasis.